Multi-risk-scenarios flexibility evaluation model of regional power grid considering economic efficiency of dispatching measures - ZHOU Qihang; GUAN Lin; XIAN Weihong; XUAN Peizheng; CHENG Lanfen; LI Zixi (电力工程技术)
Because of the integration of large amount of new energy sources, the power flow variation and voltage volatility in regional power system increase and it escalates the risk of equipment overload. In face of the uncertainty of new energy power, quick and accurate identification of the overload risk scenarios, and optimal utilization of various flexible resources from the source-grid-load parties to eliminate potential operational risks, are the urgent demands for the secure operation of the regional power grids. The flexibility evaluation indexes for the regional power grid are proposed, i.e. the flexibility demand index, the flexibility margin index and the flexibility resource utilization index, which comprehensively measure the requirements, resource and operation level of a regional power system for flexible operation. Under the target of the flexibility measurement, the mathematical models and computational method considering multiple risk scenarios are proposed, and the operation mode adjustment and the open-loop points scheduling are taken into account as the control measures. Case studies validate the feasibility and superiority of the proposed flexibility evaluation model, in comparison with the traditional boundary scenario analysis. The test results indicate that the proposed indicators, models, and algorithm can reflect the requirements and capabilities of regional power grids for operational flexibility with consideration of rich risk scenarios. The obtained dispatch solutions take into account both the economic and comprehensive aspects of various flexibility dispatch measures.